2020
DOI: 10.1021/acsearthspacechem.0c00195
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Ferrihydrite to Goethite and the Fate of Plutonium

Abstract: Understanding interactions between plutonium and iron (oxy)hydroxide minerals is necessary to gain a predictive understanding of plutonium environmental mobility and ensuring long-term performance of nuclear waste repositories. Plutonium sorption and desorption reactions with mineral surfaces, formation of PuO2 nanoparticles, and coprecipitation processes are all likely important processes under a range of geochemical conditions. We investigated plutonium fate during the formation of ferrihydrite and its subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 92 publications
(263 reference statements)
1
7
0
Order By: Relevance
“…The absence of Sn in goethite confirms the remobilization of Sn during the transformation. The released Sn is deposited in the secondary cassiterite (Balboni et al, 2020), as the ultimate sink of Sn, the most common and stable Sn mineral at the Earth's surface (Lottermoser and Ashley, 2006;Rai et al, 2011). The resistance of cassiterite to weathering was also observed from oxide zones of supergene deposits (Nickel, 1984) and supports the findings of this study.…”
Section: Enhanced Weatheringsupporting
confidence: 85%
“…The absence of Sn in goethite confirms the remobilization of Sn during the transformation. The released Sn is deposited in the secondary cassiterite (Balboni et al, 2020), as the ultimate sink of Sn, the most common and stable Sn mineral at the Earth's surface (Lottermoser and Ashley, 2006;Rai et al, 2011). The resistance of cassiterite to weathering was also observed from oxide zones of supergene deposits (Nickel, 1984) and supports the findings of this study.…”
Section: Enhanced Weatheringsupporting
confidence: 85%
“…muscovite, quartz, hematite) has been demonstrated to occur by the precipitation of PuO 2 -like nanoparticles thus strengthening the interest of the community. 39,[54][55][56][57][58][59][60][61] Because the migration ability of An(IV) colloids is highly related to the particle size, stability, and chemical reactivity, there is an obvious interest in their rigorous characterization. 53 Evidence of Pu nanoparticles as colloidal or particle fractions has also been reported in oceans, seawaters and marine sediments.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that Pu sorption on ferrihydrite followed by transformation into goethite produces PuO 2 and Pu is incorporated into the Fe mineral. Differently, co‐precipitation of ferrihydrite and Pu only results in Pu incorporation into the structure of the Fe minerals [129] . In another study, the same group investigated the interaction of Pu with calcite with EXAFS.…”
Section: Study On Soluble Inorganic Nanostructures With Multi‐modes O...mentioning
confidence: 99%
“…Differently, coprecipitation of ferrihydrite and Pu only results in Pu incorporation into the structure of the Fe minerals. [129] In another study, the same group investigated the interaction of Pu with calcite with EXAFS. They found that Pu(VI) is incorporated as plutonyl into the calcite structure and undergoes partial reduction to Pu(V).…”
Section: Oxide Nanoparticles and Colloidsmentioning
confidence: 99%